PERSPEKTIF PERCOBAAN ATAU PERMUFAKATAN JAHAT DALAM TINDAK PIDANA NARKOTIKA GOLONGAN I : Perspectives of Attempt or Criminal Conspiracy in Category I Narcotics Crimes - Saskia Camilla; Azmi Syahputra (Reformasi Hukum Trisakti, 2024)
Attempt or Evil Conspiracy in the Crime of Class I Narcotics refers to actions where individual attempts or conspires to possess, store, or receive Class I narcotic substances. The key issue examined is whether these actions constitute the criminal offense of Attempt or Conspiracy in the Crime of Class I Narcotics, specifically in the context of Decision Number 282/Pid.Sus/2022/PN.Jkt.Pst. Additionally, the study investigates the types of attempts made by the perpetrator and evaluates whether the verdict aligns with the objectives of punishment. The research utilizes a descriptive normative legal approach, analyzing secondary materials qualitatively with deductive inference. The findings indicate that the acquittal of the perpetrator for attempted conspiracy in the Class I Narcotics Crime, as per Decision Number 282/Pid.Sus/2022/PN.Jkt.Pst, is inappropriate. The perpetrator's actions constitute a form of halted or obstructed attempt, which should be recognized as an offense. The conclusion drawn is that the perpetrator indeed committed an attempt to engage in a narcotics crime, and the verdict fails to meet the objectives of punishment. This highlights the need for a thorough reassessment of the legal interpretation of attempts and conspiracies within narcotics crimes to ensure that judicial decisions effectively serve their intended purpose of deterrence and justice